Procedimientos contables y administrativos para la contratación de pólizas de seguros en las instituciones bomberiles. - Cordova Minalla, Marlene Del Rocio (My University, 2020)
In Ecuador, the institutions of the State, maintain as a general purpose to meet the needs of the population in which it develops and for the faithful fulfillment of it, they have public resources under their disposition, custody and guardianship; the same that, must be protected against any fortuitous event that could arise and will damage its integrity and conservation. In accordance with the allegations, the objective of the research is to establish the accounting and administrative procedures for the contracting of insurance policies in the fire departments, to diagnose the level of application with regulations and technical standards of government accounting imposed to this item, consistent with the provisions of the International Public Sector Accounting Standard (IPSAS). The study has a qualitative approach, the process information was obtained from the legal base section of platform of the Ministry of Economy and Finance and the State Comptroller General. In the research results, it was observed that administratively public institutions have as guidelines that, the servers responsible for the management of goods present a guarantee allowing them to cover during the period to perform functions within the institution to safeguard the integrity and quality of resources granted, while in the accounting field there are six entries for this activity, destined to the accounting of the accrued, the payment for the contracting of the insurance policy, the cancellation of the tax to the provider of this service and the corresponding adjustments of the case.
En Ecuador, las instituciones del Estado, mantienen como propósito general satisfacer las necesidades de la población en la que se desarrolla y para el fiel cumplimiento de ello, tienen recursos públicos bajo su disposición, custodia y tutela; los mismos que, deberán estar protegidos ante cualquier hecho fortuito que pudiese suscitarse y perjudique su integridad y conservación. En conformidad a lo alegado, la presente investigación tiene como objetivo establecer los procedimientos contables y administrativos para la contratación de pólizas de seguros en los cuerpos de bomberos, para diagnosticar el nivel de aplicación de los reglamentos y normas técnicas de contabilidad gubernamental impuestos a este rubro, congruente a lo establecido en la Norma Internacional de Contabilidad del Sector Público (NICSP). El estudio tiene un enfoque cualitativo, la información de los procesos se obtuvo de la sección de base legal de la plataforma del Ministerio de Economía y Finanzas y la Controlaría General del Estado. En los resultados investigativos, se observó que administrativamente las instituciones públicas tienen como pautas que, los servidores responsables del manejo de bienes presenten una garantía permitiendo cubrir a estos durante el periodo a desempeñar funciones dentro de la institución para salvaguardar la integridad y calidad de los recursos otorgados, mientras en el ámbito contable se registran seis asientos por esta actividad, destinadas a la contabilización del devengado, el pago por la contratación de la póliza de seguro, la cancelación del impuesto al proveedor de este servicio y los correspondientes ajustes del caso.
Keywords: CUERPOS DE BOMBEROS; NICSP; CONTRATACIÓN; PÓLIZAS; CONTABILIDAD GUBERNAMENTAL